Numerical Design and Studies of Multipurpose Concentrated Solar Thermal Heating System - Mukesh B.S.; Mukhopadhyay S.; Mondal A.; Chandra L. (My University, 2025)
Solar thermal energy systems are future sustainable solutions for both domestic as well as industrial use. Solar thermal systems, operating in medium temperature range (373–673 K), require concentrated solar thermal heating (CSH). In this work, a comprehensive numerical tool is developed to design and study multipurpose on-sun CSH system. The model uses a combined Monte-Carlo ray tracing, finite difference method, and all heat transfer modes. The model is validated with in-house experiment, which demonstrates its predictive capability. Next, the tool is used to optimize the cavity receiver geometry and predict the performance of the optimized CSH system under different direct normal irradiance (DNI) conditions. A CSH system using Therminol D12 as heat transfer fluid (HTF) is presented. Therminol D12 HTF-based system is predicted to take longer time than the system using water as HTF, for heating water to a specified temperature because of the heat exchanger effectiveness. However, the designed CSH system using Therminol D12 can attain higher temperatures than water without pressurization and through the heat exchanger can be used as a multipurpose system suitable for cooking, laundry, sterilization, process industry, etc. Copyright © 2021 by ASME.